Internal
problem
ID
[5267]
Book
:
Ordinary
differential
equations
and
their
solutions.
By
George
Moseley
Murphy.
1960
Section
:
Various
24
Problem
number
:
676
Date
solved
:
Monday, January 27, 2025 at 10:50:50 AM
CAS
classification
:
[[_homogeneous, `class A`], _rational, _dAlembert]
Time used: 1.217 (sec). Leaf size: 381
\begin{align*}
y \left (x \right ) &= \frac {x}{{\left (\left (-c_{1} x^{3}+\sqrt {c_{1}^{2} x^{6}+1}\right ) c_{1} x^{3}\right )}^{{1}/{3}}} \\
y \left (x \right ) &= \frac {x}{{\left (-\left (c_{1} x^{3}+\sqrt {c_{1}^{2} x^{6}+1}\right ) x^{3} c_{1} \right )}^{{1}/{3}}} \\
y \left (x \right ) &= \frac {4 x}{\left (1+i \sqrt {3}\right )^{2} {\left (\left (-c_{1} x^{3}+\sqrt {c_{1}^{2} x^{6}+1}\right ) c_{1} x^{3}\right )}^{{1}/{3}}} \\
y \left (x \right ) &= \frac {4 x}{\left (i \sqrt {3}-1\right )^{2} {\left (\left (-c_{1} x^{3}+\sqrt {c_{1}^{2} x^{6}+1}\right ) c_{1} x^{3}\right )}^{{1}/{3}}} \\
y \left (x \right ) &= \frac {4 x}{\left (i \sqrt {3}-1\right )^{2} {\left (\left (-c_{1} x^{3}+\sqrt {c_{1}^{2} x^{6}+1}\right ) c_{1} x^{3}\right )}^{{1}/{3}}} \\
y \left (x \right ) &= \frac {4 x}{\left (1+i \sqrt {3}\right )^{2} {\left (\left (-c_{1} x^{3}+\sqrt {c_{1}^{2} x^{6}+1}\right ) c_{1} x^{3}\right )}^{{1}/{3}}} \\
y \left (x \right ) &= \frac {4 x}{\left (1+i \sqrt {3}\right )^{2} {\left (-\left (c_{1} x^{3}+\sqrt {c_{1}^{2} x^{6}+1}\right ) x^{3} c_{1} \right )}^{{1}/{3}}} \\
y \left (x \right ) &= \frac {4 x}{\left (i \sqrt {3}-1\right )^{2} {\left (-\left (c_{1} x^{3}+\sqrt {c_{1}^{2} x^{6}+1}\right ) x^{3} c_{1} \right )}^{{1}/{3}}} \\
y \left (x \right ) &= \frac {4 x}{\left (i \sqrt {3}-1\right )^{2} {\left (-\left (c_{1} x^{3}+\sqrt {c_{1}^{2} x^{6}+1}\right ) x^{3} c_{1} \right )}^{{1}/{3}}} \\
y \left (x \right ) &= \frac {4 x}{\left (1+i \sqrt {3}\right )^{2} {\left (-\left (c_{1} x^{3}+\sqrt {c_{1}^{2} x^{6}+1}\right ) x^{3} c_{1} \right )}^{{1}/{3}}} \\
\end{align*}
Time used: 6.764 (sec). Leaf size: 352
\begin{align*}
y(x)\to \sqrt [3]{x^3-\sqrt {x^6-e^{6 c_1}}} \\
y(x)\to -\sqrt [3]{-1} \sqrt [3]{x^3-\sqrt {x^6-e^{6 c_1}}} \\
y(x)\to (-1)^{2/3} \sqrt [3]{x^3-\sqrt {x^6-e^{6 c_1}}} \\
y(x)\to \sqrt [3]{x^3+\sqrt {x^6-e^{6 c_1}}} \\
y(x)\to -\sqrt [3]{-1} \sqrt [3]{x^3+\sqrt {x^6-e^{6 c_1}}} \\
y(x)\to (-1)^{2/3} \sqrt [3]{x^3+\sqrt {x^6-e^{6 c_1}}} \\
y(x)\to 0 \\
y(x)\to \sqrt [3]{x^3-\sqrt {x^6}} \\
y(x)\to -\sqrt [3]{-1} \sqrt [3]{x^3-\sqrt {x^6}} \\
y(x)\to (-1)^{2/3} \sqrt [3]{x^3-\sqrt {x^6}} \\
y(x)\to \sqrt [3]{\sqrt {x^6}+x^3} \\
y(x)\to -\sqrt [3]{-1} \sqrt [3]{\sqrt {x^6}+x^3} \\
y(x)\to (-1)^{2/3} \sqrt [3]{\sqrt {x^6}+x^3} \\
\end{align*}